ACCURACY LEVEL OF TRANSLATION PREPOSITION AND CONJUNCTION WORDS IN THE TRANSLATIONS OF D3 MANDARIN LANGUAGE STUDENTS - Adilla Syahputri; Henggar Prasetryowati; Monika Herlina; Dyah Tjaturrini; Riski Utami (Acceleration: Multidisciplinary Research Journal, 2024)
This research aims to determine the level of translation accuracy of students with intermediate-level Mandarin language proficiency, understand the tendency of using different types of dictionaries and their influence on students' translation results, and identify appropriate strategies to enhance the quality of students' translation, especially in terms of translation accuracy. Data collection was conducted through observation techniques, literature review, interviews, and questionnaires. The study focused on the translation of 介词 jiècí (prepositions) and 连词 liáncí (conjunctions) found in second-semester Mandarin language students with HSK 2 equivalent proficiency. The research results still show inaccuracies in translations done by students. Inaccuracies are often found, especially in the translation of 连词 liáncí (conjunctions). This is due to students' lack of understanding of the message context in 介词 jiècí (prepositions) and 连词 liáncí (conjunctions) found in the text. Additionally, the tendency to use Google Translate in translating texts during the learning process is a significant factor contributing to translation inaccuracies. The use of electronic Mandarin-Indonesian language dictionaries is also one of the factors leading to errors in word selection that result in translation inaccuracies.